Danzón Days : Age, Race, and Romance in Mexico - Malcomson, Hettie (Book collections on Project MUSE., 2023)
"Dancer and organizer Margarita Castro Olvera provides a focal point for an ethnography of danzón in Veracruz, the Mexican city closely associated with the music-dance genre. Hettie Malcomson draws upon on-site research among semi-professional musicians and amateur dancers like Olvera to reveal how danzón connects, and does not connect, to Blackness, joyousness, nostalgia, ageing, and romance. Challenging pervasive utopian views of danzón, Malcomson uses the idea of ambivalence to explore the frictions and opportunities created by seemingly contrary sentiments, ideas, sensations, and impulses. Her account takes readers into Black and mestizo elements of local identity in Veracruz, nostalgic and newer styles of music and dance, and the friendships, romances, and rivalries among the older women at the heart of regular danzón performance and its complex social world. Fine-grained and evocative, Danzón Days journeys to one of the genre's essential cities to provide new perspectives on aging and romance and new explorations of nostalgia and ambivalence"--